On a certain Polish mathematician: a brief summary of scientific research and achievements of Kazimierz Nikodem, professor of mathematics - Adamek, Mirosław (Annales Mathematicae Silesianae, 2024)
A brief summary of scientific research and achievements of Kazimierz Nikodem, professor of mathematics.